Leader Traits And Organisational Performance In The Private Higher Education Industry In Malaysia - Sivakumaran, Vinesh Maran (2019)
The education industry is an industry which is seeing continuous growth and changes in any country in the world today. The very fact that more and more education institutions are coming up brings about a need to have good leaders helm these education institutions. This study focuses on organisation performance because it has been proven through literature that organisation performance of private higher education institutions are not up to standard or expectation, thus affecting their survival. Therefore, this study intends to look at whether organisation performance can be affected by particular traits possessed by the leaders of these private higher education institutions throughout Malaysia. The theoretical framework was formulated based on previous literature review and it resulted in the formation of this research framework.